PENGENDALIAN KUALITAS PRODUK TEH DENGAN MENGGUNAKAN METODE SIX SIGMA DMAIC PADA PT. CANDI LOKA DI JAMUS NGAWI JAWA TIMUR - Selvia Luwinda; Erni Widajanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
PT Candi Loka in Jamus is a private company engaged in large-scale tea production. The purpose of this study was to determine the sigma level value in the green tea drying process, to determine the factors that can affect defects, and to identify ways to reduce or minimize the occurrence of defects in the green tea drying process at PT Candi Loka. This study used the Six Sigma and Failure Mode and Effect Analysis (FMEA) methods with the DMAIC (Define, Measure, Analyze, Improve, Control) stages used to improve the quality of the green tea drying process at PT Candi Loka to minimize defects that occur. the results of the DPMO calculation and the sigma value obtained were the overall DPMO process value of 36,500 with a sigma value of 3.299 which means that it takes effort to achieve a sigma value of 6.00 sigma or achieve zero defects. Based on the fishbone diagram, the factors that affect defects are human factors, machine factors, and material factors. Based on the analysis using the FMEA method, it is known that the highest Risk Priority Number (RPN) value for the old failure mode or inappropriate rolling process time is 512, and the decreased performance failure mode is 392.